The role of supportive ecosystems in nurturing resilient startups and entrepreneurship: A case of Zimbabwe - Zvavahera, Promise (Goodwood Publishing, 2025)
Purpose: Consistent with Sustainable Development Goal 8, this study explores the role of supportive ecosystems in nurturing resilient startups and entrepreneurship in Zimbabwe post-COVID-19. Research Methodology: Comprehensive relevant literature drawing on Web of Science, PubMed, Google Scholar, Scopus, ProQuest, and JSTOR was conducted using the Zimbabwe case as the investigative context. Drawing on published peer-reviewed articles and official reports as data sources, fifty-eight articles and reports were thoroughly assessed for this study. Results: The findings revealed that barriers to the growth of startups and entrepreneurial enterprises in Zimbabwe include difficulties in accessing finances, inadequate institutional support, a deficiency of mentorship networks, economic instability, infrastructure deficiencies, regulatory and bureaucratic hurdles, market constraints, and limited consumer purchasing power. The study also noted that the COVID-19 pandemic has created digital transformation and innovation opportunities for startups. Conclusion: This study concludes that the entrepreneurship ecosystem in Zimbabwe is weak and lacks most of the fundamental principles necessary for a thriving entrepreneurial environment. Limitations: Overreliance on secondary data: Depending solely on secondary data sources without primary research may limit the depth of insights and understanding of local nuances and contexts. Contribution: This study emphasizes the value of encouraging public-private partnerships and global alliances to support entrepreneurial ecosystems. This strategy can boost social inclusion, increase job opportunities, and promote economic growth. This study argues that fostering a supportive environment for startups and entrepreneurship can significantly empower emerging economies during post-pandemic recovery efforts.